2018
DOI: 10.1250/ast.39.130
|View full text |Cite
|
Sign up to set email alerts
|

Effects of syllable position and vowel context on Japanese /r/: Kinematic and perceptual data

Abstract: In order to investigate the articulatory processes involved in producing Japanese /r/, we obtained speech recordings for native talkers of standard Japanese using an electromagnetic articulography (EMA) system. Each talker produced repetitions of /r/ in a carrier phrase designed to contrast syllable (CV and VCV VCV) and vowel (/a/, /i/, /u/, /e/, and /o/) contexts. Kinematic recordings were made using tongue (tip, TT; dorsum, TD; body, TB; left lateral, TLL; and right lateral, TRL) and lower lip/jaw (LL) senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A study by Dromey et al (2018), who tested sensor habituation, found that after ten minutes, participants reached a level of habituation to the sensors that did not improve even if the habituation stage lasted longer. In general, if researchers include a sensor habituation stage, it is most often 5-10 minutes of informal conversation (e.g., Katz, Mehta, & Wood, 2018;Goozée et al, 2007).…”
Section: General Sensor Placement Informationmentioning
confidence: 99%
“…A study by Dromey et al (2018), who tested sensor habituation, found that after ten minutes, participants reached a level of habituation to the sensors that did not improve even if the habituation stage lasted longer. In general, if researchers include a sensor habituation stage, it is most often 5-10 minutes of informal conversation (e.g., Katz, Mehta, & Wood, 2018;Goozée et al, 2007).…”
Section: General Sensor Placement Informationmentioning
confidence: 99%
“…The results show that the sensors placed on the articulators provide precise details of integrity and functional status of the muscle groups at each stage of the speech production process from respiration up to articulation. In Katz et al (2018), the authors have used tongue sensors for characterizing American English alveolar consonants such as/l/,/z/ and/d/ uttered by normal speakers. It was concluded that the data acquired using the tongue tip sensor provided the highest amount of useful information in distinguishing these consonants.…”
Section: Introductionmentioning
confidence: 99%
“…All the above-discussed analyzes (Frank, 2011; Lee et al , 2017; Pattem et al , 2018; Mefferd and Dietrich, 2020; Wang et al , 2016a; Katz et al , 2018) are performed using articulatory sensors for assessment of the speech. In Wang et al (2016a) only the tongue and lip sensors are considered to be optimal for the assessment for speech.…”
Section: Introductionmentioning
confidence: 99%